The Emergence of the Global Sumud Flotilla: Exposing the Moral-Institutional Paradox of Mainstream Humanitarianism - Aamina Urooj (Bulan Sabit Merah Indonesia, 2026)
This paper examines the emergence of the Global Sumud Flotilla through the lens of critical humanitarianism, which raises implicit questions about the structural and moral limits of institutional humanitarianism in the context of long-held political violence in Gaza. For the purpose of limiting the analysis, the paper focuses on UNRWA, WFP, and ICRC and argues that their constrained engagement during Israel’s siege of Gaza is the manifestation of a moral-institutional paradox. Bound by donor politics and the norm of apolitical neutrality, these organizations remained limited to issuing normative condemnations and providing minimal relief under restrictive conditions. On the other hand, the Global Sumud Flotilla, one of the largest solidarity-based flotilla mobilizations to date, showed flotilla activism as the process of repoliticizing humanitarianism, rooted in solidarity, resistance, and direct confrontation with injustice rather than depoliticizing relief. Employing a qualitative exploratory research methodology, this study aims to highlight the comparative analysis of mainstream humanitarian groups’ limited action constrained by moral-institutional paradox to the Global Sumud Flotilla’s grassroots activism as an attempt to repoliticize the humanitarian activism and signals the rise of a new moral practice of transnational solidarity.